An empirical study on cultivating college students' cross-cultural communicative competence based on the artificial-intelligence English-teaching mode - Long, Jingjing; Lin, Jiaxin (Frontiers in Psychology, 2022)
Artificial intelligence education must be an important part of information technology education in the future. It will enter the classroom in various forms and enter the learning life of students. The modern teaching media used in university artificial intelligence courses not only include some conventional teaching courseware, multimedia videos, and tool software, but also some teaching media unique to artificial intelligence, such as smart software, smart devices, smart websites, and so on. In this study, the existing cross-cultural competence dimensions and evaluation scales at home and abroad are theoretically explained, and factor analysis. Through the comparison and selection of comprehensive evaluation methods. Its main advantages are: simple mathematical model and easy operation. Construction of a comprehensive evaluation model for college students' cross-cultural competence includes the principles and ideas of model construction, the methods and steps of model construction, and model calculations. In the survey results, the four-level scores of all samples have a significant positive correlation with foreign cultural knowledge, attitudes and cross-cultural communication skills at 0.01 level (bilateral) and 0.05 (bilateral) respectively.